Analisis Pengaruh Pemasaran Melalui Pendekatan Bauran Pemasaran (7p) Terhadap Keputusan Berkunjung Wisatawan Di Taman Wisata Alam Mangrove Angke Kapuk Jakarta - Familya Putri, Kezia; Facrureza, Dewanta (CV RIFAINSTITUT, 2023)
Judging by the existence of an increasing tourism development, there are also more and more competitors in the tourism industry, especially in nature conservation tourism. In facing competition, maintaining excellence, and developing tourism objects, it is necessary to have a special strategy in marketing, because marketing has an important role in the success of a tourist destination, and to always achieve profits. The purpose of this study was to determine the effect of the marketing mix (7P) on the decision to visit tourists at the Angke Kapuk Mangrove Nature Park. The research method used is quantitative. Determination of the sample using the techniquenon-probability sampling withpurposive sampling method with the number taken is 100 respondents. This study uses multiple linear regression analysis. Based on the results of the t test it is known that partially variableproduct (X1),place (X4), people (X5),process (X6) has a positive and significant effect on the decision to visit (Y), then for variablesprice (X2),promotion (X3),physical evidence (X7) has no positive and insignificant effect on the decision to visit (Y). In the F test, it was obtained that the marketing mix variable (7P) had a simultaneous effect on visiting decisions. Based on the R test2 obtained a value of 0.716. This states that as much as 71.6% of Tourist Visit Decisions are influenced by variables from the Marketing Mix (7P), while the remaining 28.4% are influenced by other variables outside the X variable.Variable conclusionproduct (X1),place (X4), people (X5),process (X6) partially has a positive and significant effect on the decision to visit (Y), while for variables price (X2), promotion (X3), physical evidence (X7) partially has no positive and insignificant effect on the decision to visit (Y).